El sendero de los nidos de arana - Calvino, Italo (Biblioteca Calvino (Ediciones Siruela), 2012)
Pin, a young cobbler's apprentice in a town on the Ligurian coast during World War II, becomes involved with a band of partisans after a mishap with a Nazi soldier.